2000
DOI: 10.1038/sj.onc.1203463
|View full text |Cite
|
Sign up to set email alerts
|

Allelotyping defines minimal imbalance at chromosomal region 17q25 in non-serous epithelial ovarian cancers

Abstract: Allelic deletions of multiple chromosome 17q loci in sporadic ovarian cancer of epithelial origin suggest that inactivation of tumor suppressor gene(s) in these regions may be important for ovarian tumorigenesis. To further de®ne the pattern of allelic imbalance in epithelial ovarian tumors of di erent histologies, a PCR-based assay was used to assess loss of heterozygosity (LOH) of polymorphic markers representative of TP53, BRCA1, NME1 and GH1, and region 17q23-25. LOH was observed for at least one marker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 40 publications
(71 reference statements)
4
49
0
Order By: Relevance
“…Tumour samples and peripheral blood lymphocytes were collected with informed consent from participants undergoing surgeries performed at the Research Centre of the University of Montreal Hospital Centre (CRCHUM)-Notre Dame Hospital site or from surgeries performed at the McGill University Health Centre -Montreal General Hospital as described (21,33). Clinical features such as disease stage, and tumour characteristics such as grade and histopathological subtype, were assigned by a gynecologiconcologist and/or gynecologic-pathologist according to the criteria established by the International Federation of Gynecology and Obstetrics as reported in previous studies for some cases (21,22,34) and summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour samples and peripheral blood lymphocytes were collected with informed consent from participants undergoing surgeries performed at the Research Centre of the University of Montreal Hospital Centre (CRCHUM)-Notre Dame Hospital site or from surgeries performed at the McGill University Health Centre -Montreal General Hospital as described (21,33). Clinical features such as disease stage, and tumour characteristics such as grade and histopathological subtype, were assigned by a gynecologiconcologist and/or gynecologic-pathologist according to the criteria established by the International Federation of Gynecology and Obstetrics as reported in previous studies for some cases (21,22,34) and summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these genes, DPH1 (17p13.3), HIC1 (17p13.3), NF1 (17q11.2), and RARA (17q21.1), have also been proposed to function as TSGs in EOC (11)(12)(13)(14). Unique loci exhibiting a high frequency of LOH have also been identified, suggesting the possibility of new TSGs in ovarian cancer (15)(16)(17)(18)(19)(20)(21)(22). It is thus likely that several genes act in concert in suppressing tumourigenicity and thus account for the unusually high frequency of LOH that often involves an entire chromosome 17 contig in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, p53 mutations may affect malignant transformation of endometriosis into EAC (16) 17q. The histologies of EOC displaying a pattern of 17q deletions were of the EAC, CCC and mucinous types (33). Tumor suppressor genes on 17q are possibly involved in development of endometriosis (2,34).…”
Section: Loh Involved In Clear Cell Carcinoma (Ccc) Of the Ovary: Thementioning
confidence: 99%
“…doi:10.1038 Keywords: ovarian cancer; cell lines; DNA microarray; chromosome 17; gene expression Epithelial ovarian cancer (EOC) is the second most common gynecological cancer and is responsible for almost half of deaths associated with gynecological pelvic malignancies. The molecular genetic analysis of EOC has revealed a significant role for chromosome 17 genes in the pathogenesis of ovarian malignancies through loss of heterozygosity (LOH) and karyotype studies (Eccles et al, 1990;Lee et al, 1990;Russell et al, 1990;Sato et al, 1991;Foulkes et al, 1993;Phillips et al, 1993;Tavassoli et al, 1993;Mertens et al, 1997;Dion et al, 2000). The frequent reduction to hemizygosity implies that numerous genes on both arms of chromosome 17 are implicated in EOC.…”
mentioning
confidence: 99%
“…A number of genes on the long arm of chromosome 17 also have been shown to be implicated in EOC: the ERBB2 oncogene at 17q21.1 (Slamon et al, 1989), the hereditary breast/ ovarian cancer TSG BRCA1 at 17q21.1 (Miki et al, 1994;Merajver et al, 1995) and the NME1 tumor metastasis marker gene at 17q21.3 (Mandai et al, 1994;Leary et al, 1995;Schneider et al, 1996Schneider et al, , 2000. In addition to the known genes implicated in ovarian tumorigenesis, LOH analysis and/or karyotype studies revealed the locations of novel TSGs on the long arm of chromosome 17 coincident with 17q21 (Tangir et al, 1996), 17q21-23 (Jacobs et al, 1993;Yang-Feng et al, 1993;Godwin et al, 1994), 17q23-qter (Mertens et al, 1997) and 17q25 (Kalikin et al, 1997, Dion et al, 2000. Other mechanisms not detected by these methods such as alterations in methylation patterns and alterations in promoter activity may be invoked, which alter the expression of genes.…”
mentioning
confidence: 99%